2003
DOI: 10.1590/s0100-879x2003000200013
|View full text |Cite
|
Sign up to set email alerts
|

Priming effects of a peripheral visual stimulus in simple and go/no-go tasks

Abstract: The early facilitatory effect of a peripheral spatially visual prime stimulus described in the literature for simple reaction time tasks has been usually smaller than that described for complex (go/no-go, choice) reaction time tasks. In the present study we investigated the reason for this difference. In a first and a second experiment we tested the participants in both a simple task and a go/no-go task, half of them beginning with one of these tasks and half with the other one. We observed that the prime stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
3
0
3
Order By: Relevance
“…According to the latter, attention mobilization by a cue would be related to the difficulty of the task (4,5). As the difficulty of the discrimination increases more attention would be dedicated to the task, tonically facilitating not only central processing of the targets but also that of the cue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the latter, attention mobilization by a cue would be related to the difficulty of the task (4,5). As the difficulty of the discrimination increases more attention would be dedicated to the task, tonically facilitating not only central processing of the targets but also that of the cue.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy normally used in any one of these tasks could change if a task were performed after the other. Squella and Ribeiro-do-Valle (5) showed that the attentional effect produced by a gray ring in a go/no-go reaction time task when a white vertical line inside a ring was the positive target could completely disappear if the volunteers were previously tested with the same stimuli in a simple reaction time task. The exact mechanism of these attentional strategies is not clear.…”
Section: Experiments 1 and 2)mentioning
confidence: 99%
“…When they have to respond differentially to two simple visual stimuli, latencies increase to about 350 to 450 ms (1). The occurrence of another sensory stimulus (auditory, visual) preceding the target visual stimulus usually shortens reaction time by tens of milliseconds (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…Porém, no Brasil, as publicações enfocando os estudos no paradigma de priming, mesmo não restritos ao contexto do processamento de leitura, são escassas (Azevedo, Squella & Ribeiro-do-Valle, 2001;Busnello, 2007;Carreiro, Haddad Júnior & Baldo, 2003;DelFava & Ribeiro-do-Valle, 2004;Macedo, 2003;Oliveira, 2001;Oliveira & Janczura, 2004;Pompéia & Bueno, 2006;Pompéia, Paes & Bueno, 2003;Rosin, 2001Rosin, , 2004Squella & Ribeiro-do-Valle, 2003), conforme pesquisa feita nas bases de dados Scielo e LILACS, com a palavra-chave "priming".…”
unclassified